Measurement of Corporate Social Responsibility : Comparative Genre Analysis as a Method of Contrasting CSR Performance between Two Firms - Corvest, Aymeric; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This exploratory study introduces genre analysis as a linguistic tool for examining CSR reports, focusing on the ESG performance of Southwest Airlines and Delta Air Lines. Utilising comparative genre analysis, it investigates move-structure analysis, thematic analysis, text analysis, and visual genre analysis to reveal patterns and rhetorical strategies in their CSR narratives. This study uncovers distinct CSR strategies between the firms, particularly regarding topic utilisation, emission reduction and aviation fuel. Differing narratives are also identified, with Southwest Airlines adopting a top-down approach. The findings provide strategic value for enhancing CSR performance and reporting, offering practical business implications for strategic management, such as benchmarking, competitor analysis, identifying trends, and recognising best practices.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses